"Without this program, women can lose their lives": migrant women's experiences with the Safe Abortion Referral Programme in Chiang Mai, Thailand. Issue 51 (30th November 2017) - Tousaw, Ellen; La, Ra Khin; Arnott, Grady; Chinthakanan, Orawee; Foster, Angel M.
Abstract: For displaced and migrant women in northern Thailand, access to health care is often limited, unwanted pregnancy is common, and unsafe abortion is a major contributor to maternal death and disability. Based on a pilot project and situational analysis research, in 2015 a multinational team introduced the Safe Abortion Referral Programme (SARP) in Chiang Mai, Thailand, to reduce the socio-linguistic, economic, documentation, and transportation barriers women from Burma face in accessing safe and legal abortion care in Thailand. Our qualitative study documented the experiences of women with unwanted pregnancies who accessed the SARP in order to inform programme improvement and expansion. We conducted 22 in-depth, in-person interviews and analysed them for content and themes using deductive and inductive techniques. Women were overwhelmingly positive about their experiences using the SARP. They reported lack of costs, friendly programme staff, accompaniment to and interpretation at the providing facility, and safety of services as key features. Financial and legal circumstances shaped access to the programme and women learned about the SARP through word-of-mouth and community workshops. After accessing the SARP and receiving support, women became community advocates for reproductive health. Efforts to expand the programme and raise awareness in migrant communities appear warranted. Our findings suggest that referral programmes for safe and legal abortion can be successful in settings with large displaced and migrant populations. Identifying ways to work within legal constraints to expand access to safe services has the potential to reduce harm from unsafe abortion even in humanitarian settings.